MONITORING SUDUT FASA MENGGUNAKAN MIKROKONTROLER BERBASIS INTERNET OF THINGS (IOT) - ramly rasyid; Miftah Muhammad; Rahman R Rasyid (Journal of Science and Engineering, 2023)
Phase angle is very important in determining active power and reactive power parameters in AC power sources so it needs to be monitored. This research created a phase angle monitoring tool based on the Internet of Things (IoT) using the blynk application, apart from monitoring phase angles it also monitors voltage, current and power factor. The method used is an experimental method, which starts with hardware design using a Node MCU where the Node MCU will later convert analog electrical quantities to digital while the PZEM 004-V30 sensor contains a voltage sensor and a current sensor which detects analog quantities sent to Node MCU, software design using Arduino IDE and IoT using the Blynk application then testing the tool created. Testing for measuring and monitoring phase angles and reactive power will be compared with the Haiko clamb meter so that the measurement error presentation can be seen. The presentation of phase angle measurement errors for loads of 1x36 Watt, 2x36 Watt, 3x36 Watt and 4x36 Watt respectively are 4.32%, 3.40%, 1.77% and 1.32%. The error is below 5%, so the performance of this tool can be said to be good. The highest error presentation was 4.52% for the 1x36 Watt TL lamp load, while the smallest error presentation was 1.32% for the 4x36 Watt TL lamp load.